Application of Ketone-Based Resins as Anticorrosive Coating. (22nd December 2010) - Sezer, Esma; Kızılcan, Nilgün; Çoban, Kerim
Abstract : Effect of some newly synthesized modified ketonic resins on corrosion inhibition of stainless steel (SS) and copper (Cu) was investigated in acidic medium. Carboxyl, hydroxyl, and carbonyl functionalized resins have been coated on metal electrode as a thin film by dipping method. Corrosion characteristics of coating on SS (304 L) and Cu were investigated by polarization, open-circuit, and impedance measurement. These measurements performed at different time and the stability of polymeric coating were tested with time in acidic medium. The resin coating was able to protect both the SS and copper.